Greening the Greyfields New Models for Regenerating the Middle Suburbs of Low-Density Cities - Newton, Peter W.; Newman, Peter W.G.; Glackin, Stephen; Thomson, Giles; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This open access book outlines new concepts, development models, governance and implementation processes capable of addressing the challenges of transformative urban regeneration of cities at precinct scale.
1. The Global Greyfields Transition: Why Urban Redevelopment in Low-Density, Car-Based Middle Suburbs Needs a New Model -- 2. The Greyfield Challenge to Australian Governments -- 3. Distributed Green Technologies for Regenerating Greyfields -- 4. Transport and Urban Fabrics$1 (BMoving from TODs to TACs with Greyfield Regeneration -- 5. Climate Resilience and Regeneration$1 (BHow Precincts Can Adapt to and Mitigate Climate Change -- 6. Changing Attitudes to Housing and Residential Location in Cities --- The Cultural Clash and the Greyfield Solution -- 7. Planning, Design, Assessment, and Engagement Processes for Greyfield Precinct Regeneration -- 8. Integrating Transition Processes for Regenerating the Greyfields.s
Keywords: Geography; Landscape architecture; Human geography; Regional Geography; Landscape Architecture; Human Geography